الإعجاز القرآني في الصيغ الصرفية (Revue El-Wahat pour les Recherches et les Etudes, 2023)
Abstract: The Qur’anic Miracle Preoccupied The Thought Of Scholars From The Earliest Times The Qur’an Was Revealed To The Heart Of The Messenger Of God, May God’s Prayers And Peace Be Upon Him. However, The Idea Of Researching The Aspects Of The Miracles Of The Noble Qur’an Was Not Proposed In The Time Of The Prophet, May God’s Prayers And Peace Be Upon Him, And The Time Of The Rightly Guided Caliphs - May God Be Pleased With Them -. But It Was Presented Later After The Expansion Of The Islamic State And The Mixing Of Muslims With Different Races Who Are Not Arabs, And Muslims Opened Up To The Cultures Of Others And Were Influenced By Them, So The Sayings Of Philosophers Appeared, And The Science Of Theology Appeared In Different Sects And Schools, And Through Research In The Science Of Theology, The Research On The Qur’anic Miracle And The Expression Of The Faces Of Its Miracles Emerged, And He Mentioned The Scholars Have Various Facets Of Metaphysical, Educational, Linguistic, And Other Legislative Aspects, And The Latter Is The Subject Of Our Research And It Is Related To The Qur’anic Miracle In Morphological Formulas And Its Effect On Achieving The Miracle Aspect Of Qur’an Expression.Key Words: Quranic Miracles; Morphological Formulas; Verb Tenses; Noun Formulas;